Studies on the nutritive values of cowpeas, sunflower oilcake, Geotrichum candidum and the relationships between bioavailable energy estimates for pigs and poultry - Nell, Francois Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1992.